2020
DOI: 10.1186/s12917-020-02608-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of therapeutic-dose induced intestinal enrofloxacin concentrations in healthy pigs on fecal Escherichia coli populations

Abstract: Background Knowledge of therapy-induced intestinal tract concentrations of antimicrobials allows for interpretation and prediction of antimicrobial resistance selection within the intestinal microbiota. This study describes the impact of three different doses of enrofloxacin (ENR) and two different administration routes on the intestinal concentration of ENR and on the fecal Escherichia coli populations in pigs. Enrofloxacin was administered on three consecutive days to four different treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…The result found significant changes in the gut microbial and their functional metabolite pathways in American shad after ENR treatment, which was similar to the report by Elokil et al (2020). Some researchers also found that ENR resulted in microbial metabolic disorder in the gut of chickens, mice and pigs (De Smet et al, 2020;Li, Hao, et al, 2017;Li, Long, et al, 2017;Strzepa et al, 2017). There was a significant difference in the amount of Proteobacteria between ENR exposure and the control group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The result found significant changes in the gut microbial and their functional metabolite pathways in American shad after ENR treatment, which was similar to the report by Elokil et al (2020). Some researchers also found that ENR resulted in microbial metabolic disorder in the gut of chickens, mice and pigs (De Smet et al, 2020;Li, Hao, et al, 2017;Li, Long, et al, 2017;Strzepa et al, 2017). There was a significant difference in the amount of Proteobacteria between ENR exposure and the control group.…”
Section: Discussionsupporting
confidence: 86%
“…Significant metabolic changes in the gut of mice were also found after exposure to ENR and vancomycin (Sun et al, 2019). De Smet et al (2020) found that ENR exposure impacted the faecal Escherichia coli populations in pigs. In addition, the dysbiosis of gut microbiota was found after ENR exposure to chickens and mice (Li, Hao, et al, 2017;Strzepa et al, 2017).…”
mentioning
confidence: 99%
“…The high dose results in a higher concentration of enrofloxacin and its metabolite in the system, which means that the clearance time is extended [ 55 ]. Studies have shown that enrofloxacin and its metabolites are excreted from the plasma to the intestinal lumen through the active transport system, as well as enterohepatic circulation accumulates them in the intestine [ 56 , 57 ]. Furthermore, their concentrations increase from the proximal to the distal part of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that group administration of antimicrobials plays an important role in the selection of resistant bacteria [ 47 ]. Although limited information is available on intestinal exposure for the antimicrobials currently marketed, it is known that it could influence the selection of resistant bacteria [ 48 ]. In fact, incomplete oral absorption may affect the intestinal microbiota [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although limited information is available on intestinal exposure for the antimicrobials currently marketed, it is known that it could influence the selection of resistant bacteria [ 48 ]. In fact, incomplete oral absorption may affect the intestinal microbiota [ 48 ]. Several studies have highlighted that the increasing level of antimicrobial resistance in gut microbiota was mainly due to the antimicrobial misuse [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%